Compass models: Theory and physical motivations - Nussinov, Zohar; van den Brink, Jeroen (Reviews of modern physics, 2015)
The quest to achieve optimal directional radiation from microlasers has stimulated numerous investigations in the field of dielectric microresonators which play an important role in fundamental and applied research. This review focuses on a comprehensive discussion of recent results from experimental and theoretical studies ranging from tailoring resonator shapes for directed light emission, mode interactions occurring at avoided resonance crossings, and non-Hermitian physics to wave chaotic properties of dielectric microwave cavities. This is a review on theoretical and experimental studies on dielectric microcavities, which play a significant role in fundamental and applied research. The basic concepts and theories are introduced. Experimental techniques for fabrication of microcavities and optical characterization are described. Starting from undeformed cavities, the review moves on to weak deformation, intermediate deformation with mixed phase space, and then strong deformation with full ray chaos. Non-Hermitian physics such as avoided resonance crossings and exceptional points are covered along with various dynamical tunneling phenomena. Some specific topics such as unidirectional output, beam shifts, wavelength-scale microcavities, and rotating microcavities are discussed. The open microdisk and microsphere cavities are ideal model systems for the studies on wave chaos and non-Hermitian physics.